Effect of rapamycin-eluting stents on in-stent restenosis and early inflammatory response in coronary artery narrowing animal models - Jianbing Zhang; Jingyi Zhu; Baiping Sui; Ying Wang; Bingxue Zhang (Journal of Cardiothoracic Surgery)
Abstract Objective it was to evaluate the efficacy and safety of rapamycin-eluting stents at different doses in the treatment of coronary artery narrowing in miniature pigs. Methods a total of 20 miniature pigs were randomly assigned into four groups: S1 group (low-dose rapamycin-coated stent, 55 µg/mm2), S2 group (medium-dose rapamycin-coated stent, 120 µg/mm2), S3 group (high-dose rapamycin-coated stent, 415 µg/mm2), and D0 group (bare metal stent). The stent size was 3.0 mm × 18 mm, with an over-expansion ratio of 1.1. Each group consisted of five pigs. Stent implantation was followed by euthanasia and tissue collection after 1 month. Vascular measurements, inflammatory response scores, cardiovascular injury scores, endothelialization scores, liver and kidney function indices, and myocardial injury markers were compared among the groups. Results the neointimal thickness in the S2 and S3 groups was significantly lower than that in the S1 and D0 groups (S1 group: 24.08 ± 3.95, S2 group: 1.86 ± 0.28, S3 group: 2.72 ± 0.74, D0 group: 22.85 ± 3.15, P < 0.05). The residual lumen area in the S2 and S3 groups was significantly larger than that in the S1 and D0 groups (S1 group: 2.73 ± 0.51, S2 group: 4.25 ± 0.78, S3 group: 3.91 ± 0.73, D0 group: 2.91 ± 0.44, P < 0.05). The neointimal area in the S2 and S3 groups was significantly smaller than that in the S1 and D0 groups (S1 group: 3.44 ± 0.84, S2 group: 1.78 ± 0.25, S3 group: 2.07 ± 0.41, D0 group: 3.43 ± 0.72, P < 0.05). The degree of lumen narrowing in the S2 and S3 groups was significantly lower than that in the S1 and D0 groups (S1 group: 44.25 ± 3.66%, S2 group: 14.19 ± 2.01%, S3 group: 15.29 ± 2.45%, D0 group: 21.79 ± 3.51%, P < 0.05). The inflammation scores of coronary artery walls in the S2 and S3 groups of miniature pigs were markedly lower than those in the S1 and D0 groups (P < 0.05). The cardiovascular injury scores (P = 0.072) and endothelialization scores (P = 0.085) differed slightly among the four groups (P > 0.05). Post-operative liver function indicators (alanine transaminase, aspartate transaminase), kidney function indicators (blood urea nitrogen, serum creatinine), and myocardial injury markers (creatine kinase, creatine kinase-MB) also showed neglectable differences among the four groups (P > 0.05). Conclusion medium and high doses of rapamycin-eluting stents effectively inhibit neointimal hyperplasia and local vascular inflammatory response in miniature pigs without causing damage to liver and kidney functions or myocardial cells. These stents demonstrate high efficacy and safety. Rapamycin-coated coronary stents, as an effective treatment for coronary artery stenosis, may achieve further improvement in therapeutic efficacy through optimization of drug dosage and stent design.